PENERAPAN SMS GATEWAY SEBAGAI ALTERNATIF PENINGKATAN KEDISIPLINAN SISWA DI SMK ANWARUL MALIKI SUKOREJO PASURUAN - Achmat Mubarok W.H Santoso (Universitas Yudharta Pasuruan, 2017)
Implementation of sms gateway is one of school effort to keep learners behavior so as not to deviate and can encourage learners to behave in accordance with norms, rules and regulations that apply in school. Sms gateway is an online application system as a means of connecting schools with parents / guardians of students through attendance of students who are directly linked through the application, then if there are students who are not present or without explanation automatically this application will send a message to parents Learners so that with this application system parents can know the existence of his son and daughter as well as student discipline control.